Focus on entrepreneurial traits: Analysing scientific publications using bibliometrics - Kozma, Dorottya Edina; Fehér, Helga; Bosnyák-Simon, Nikolett (Vezetéstudomány / Budapest Management Review, 2023)
The present study focused on the bibliometric analysis of entrepreneurial traits in international academic journals. The bibliographic analysis has been carried out with the aim of identifying publication links related to the topic area. The authors of the study sought to identify whether the most cited authors’ studies share entrepreneurial personality traits and which countries have the largest publication network in terms of academic publications on entrepreneurial traits. The analyses were carried out in terms of institutions, countries and the number of citations of authors of the publications. The results showed that US higher education institutions lead the research on this topic, meaning that the US has the largest publication linkage network in terms of countries. Only eight authors have published studies as the basis for the citation system in this topic, which has been the subject of intense international research for several decades.